The use of virtual reality and augmented reality in psychosocial rehabilitation for adults with neurodevelopmental disorders: A systematic review - Tan, Bhing-Leet; Shi, Jing; Yang, Suyi; Loh, Hannah; Ng, Desiree; Choo, Cherie; Medalia, Alice (Frontiers in Psychiatry, 2022)
Objectives Virtual reality and augmented reality have been used in psychosocial rehabilitation for adults with neurodevelopmental disorders in recent years, to provide functional training in a scaffolded and appealing manner. This systematic review attempted to evaluate 1) how virtual reality or augmented reality technology was deployed, when used as an intervention for adults with neurodevelopmental disorders; and 2) how virtual or augmented reality-assisted psychosocial rehabilitation programs impacted on the functional domains of community living, employment and social participation. Methods The Preferred Reporting Items for Systematic Reviews and Meta- Analyses (PRISMA) guidelines was adopted and a search of publications between June 2012 and June 2022 was carried out. The target groups were adults with schizophrenia/schizoaffective disorders, autism spectrum disorder, intellectual disabilities and attention deficit hyperactivity disorder. Interventions that targeted at least one functional domain were included. Results The database search generated 1267 records and 38 studies met the inclusion criteria. Three studies utilized augmented reality while the rest utilized virtual reality. The virtual scenarios were displayed in various ways, such as head-mounted displays, computer screens, mobile devices and cave rooms. A few studies also used features such as speech recognition, eye tracking and motion-capture device to provide real-time feedback to participants during rehabilitation. Eleven studies reported interventions that addressed community living, fifteen studies addressed vocational skills and nine studies trained participants in social skills or social cognition. Three studies sought to improve quality of life using virtual scenarios to expose participants to various situations. Majority of these studies reported preliminary promising results, with improvement in the functional domains addressed. However, several studies had small sample sizes and many single-arm pretest-posttest studies were assessed to be of serious or critical risk of bias. Conclusion Virtual reality and augmented reality are deployed in various ways to augment psychosocial rehabilitation for adults with neurodevelopmental disorders. Most interventions target skills training or strategy learning in the areas of community living, work and social participation. Preliminary positive findings of their effects on functional performance were reported. Larger and robust studies using ecologically valid outcome measures will be needed to establish their effects on real-world functional outcomes.